PERAN GURU PAI DALAM PENINGKATKAN SIKAP SPIRITUALITAS SISWA MELALUI PEMBACAAN SURAT-SURAT PENDEK DI SMK PANCASILA MOJOWARNO JOMBANG - Budiyono, Ahmad; Hakim, Arif Rahman; A.S, M. Syahril (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2021)
Spiritual attitude is a reflection of religious character. Religion is a character value that is related between humans and their God, Spiritual attitudes can be implemented as a very good way to always be grateful for the blessings of Allah SWT. The results showed that the role of Islamic religious education teachers in improving students' spiritual attitudes included; consistency (istiqomah), humility (tawadu'), strive and surrender (tawakal), sincerity (sincereness), totality (kaffah), balance (tawazun), integrity and perfection (ihsan). as for a. supporting factors are adequate facilities and infrastructure, as well as a comfortable environment. b. the inhibiting factor is the limited time for meetings and interactions between teachers and students. Lack of motivation and parental attention. There is no written assessment of emotional and spiritual intelligence.